Survey of Academy of Management Authors - Lee, Sang M. (Academy of Management Journal, 1969)
The article presents a comment on an article titled ?A Profile of the Academy of Management Member,? by Professor Roderick A. Forsgren in the March 1969 issue of ?Academy of Management Journal.? In response to the previous article outlining the profile of the typical Academy of management member, the author compiled a list of the organizational affiliations, educational background, and types of articles published in the ?Academy of Management Journal.? Several tables presenting the results are included. The article shows that the journal tends to focus on organizational behavior and management theory.